DINASTI POLITIK: BASIS POLITIK DAN KEPUASAN PUBLIK - Haliim, Wimmy; Hakim, Andy Ilman (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2020)
The opening of political access in a country that was going through a period of democratic transition gave rise to